Effect of Low-Fidelity Music (lo-fi) on Reading Comprehension in Indonesian College Students at Jabodetabek - Amanda Diva Anggraita; Carmen Claudia; Rafael Angkasa Pilartomo; Sabrina Suwandi; Sheren Budiarso; Christ Billy Aryanto (Fakultas Psikologi Universitas Pancasila, 2021)
Reading comprehension is important in the process of studying. Nowadays, low-fidelity (lo-fi) music is claimed to help people study. Lo-fi music is a music aesthetic characterised by the imperfection in recording. Previous research proved that various music can either increase or decrease our reading comprehension ability. No research has been done on the effects of lo-fi music towards reading comprehension. Thus, we conduct an online experimental study on the effects of lo-fi music on the reading comprehension in university students. 100 Jabodetabek students were equally divided into control and experimental groups by randomization. Reading comprehension was tested using a reading subtest from a Cambridge Ordinary Level (O-level) test translated into the Indonesian language. The experimental group did the test while listening to lo-fi music. The control group did the test without listening to any music. The Mann-Whitney U-test concluded that the results failed to reject the null hypothesis [(​U=3545, n1=50, n2=50, p>0,05), ΣR1=230, ΣR2=223]. In conclusion, there is no effect of listening to lo-fi music towards reading comprehension in Indonesian Jabodetabek university students. Whilst studying, students may choose to listen to lo-fi music or not.